Large deflections of a cantilever beam of nonlinear bimodulus material subjected to an end moment - Baykara, C; Güven, U; Bayer, I (SAGE PUBLICATIONS LTD, 2005)
In this article, the large deflections of a thin cantilever beam under an end moment is considered. The material behavior of the beam is assumed to be nonlinear bimodulus. The aim of this study is to investigate the effect of bimodulus behavior on the horizontal and vertical deflections at the free end. The numerical results obtained are tabulated. It is shown that the bimodulus behavior has a significant effect on the large deflections.
Keywords: large deflection; cantilever beam; end moment; nonlinear modulus; exact solution; NON-LINEAR MATERIALS; Materials Science; Polymer Science